Recent trends for clean fuel using environmental protecting oxidative desulfurization process - S. Said; S. Mikhail; M. Riad (Cleaner Chemical Engineering)
The tremendous consumption of fuel oil causes the environmental pollution and it is necessary to curtail toxic sulfur compounds. The environmental remediation acquires clean desulfurization technology; oxidative desulfurization (ODS) process is intensively studied to produce sulfur clean fuels due to its mild reaction conditions, no hydrogen need and its notable desulfurization performances. This work emphasizes a comprehensive review on the recent finding in catalytic ODS including recently developed materials as metal organic framework/metal oxide composite, polyoxometalate, titanium and molybdenum oxides. The essential link between the catalyst properties and performances in ODS are discussed. The utilization of other ODS assisted processes like extractive, photo-catalytic, adsorptive, ultrasonic and mixing are also reviewed. The insights presented will aid in the development of more accurate and efficient methods for clean fuel production, thereby helping to protect human health and the environment. The review provides guidance from a methodology perspective like mixing assisted desulfurization process for future research and development. Finally, the required future works to mature this technology are suggested providing feasible outlook in efficient oxidative desulfurization technologies for clean fuel production from real fuel.